Die Rezeption und der Streit um den Roman "Im Westen nichts Neues" von E.M. Remarque in der literarischen Öffentlichkeit des Vorkriegspolen - Dziergwa, Roman (Studia Germanica Posnaniensia, 2018)
The controversy and disputes which appeared in the Polish literary criticism of the 1930s after the publication of the Polish version of Remarque's famous novel „All Quiet on the Western Front“ were based on specified political grounds. The National Democratic press, for instance, was entirely against Remarque's book and would demand to have it banned altogether. The response of the military magazines was more differentiated. The author was reproached with commonplaceness and „Germanic fetor“, however, on the other hand, he was praised for describing the firmness of the German soldiers, the sense of comradeship and the exemplary attitude of the privates towards the officers. The literary critics of the communist orientation, clustered around „Literary Monthly“ (Wat, Zawadzki) emphatically refused to acknowledge the book, which was a consequence of their total rejection of the pacifist literature of that time. This point was argued by the representatives of the liberal and pacifist intellectuals who generally approved of the book, some being even enthusiastic about it (eg. Stempowski). In this way, the polarity of political attitudes of the recipients became more apparent (vide Wat-Słonimski polemics). Thanks to it, Remarque's novel became, in a way, a „gauge“ and, at the same time, a catalyst of the public feeling of the Polish intellectuals in the early 1930s.